The genetic component to diabetes - Cox, Nancy (Henry Stewart Talks, 2007)
Diabetes mellitus: definition, classification and its use as a model for genetic studies of complex disorders, Genetic forms of diabetes mellitus: monogenic and polygenic, Identification of diabetes genes, Monogenic forms of diabetes: human HNF-1-alpha/MODY3 gene, Polygenic forms of diabetes, HLA and ISN in type 1 diabetes, Genes for type 2 diabetes and linkage mapping, TCF7L2 in type 2 diabetes, Genome wide association studies and gene loci implicated in these studies, Allelic variation in human gene expression, Ancestral susceptibility models